SISTEM PENDUKUNG KEPUTUSAN PENGGUNAAN PEWANGI SETRIKA TERFAVORIT DI SUKMAJAYA LAUNDRY MENGGUNAKAN METODE WEIGHTED PRODUCT - Aulia Nurizki; Naely Farkhatin (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2024)
In the modern era, laundry services have become a practical solution for busy people. Sukmajaya Laundry, located in a strategic area in Depok, offers various services such as kilo laundry, bed cover washing, and express washing. However, despite having a wide range of ironing fragrance options, the laundry owner faces difficulties in determining which fragrance is most preferred by customers. This study aims to assist the owner of Sukmajaya Laundry in recommending the most popular ironing fragrance to customers. With this recommendation, it is hoped that new customers will no longer struggle to choose a fragrance that suits their preferences. The research employs the Weighted Product (WP) method, which combines several attributes with weighted criteria to calculate the total value. The alternative with the highest total value will be considered the best solution. This study results in a decision support system that can recommend the most popular ironing fragrance based on previous customer preferences, thereby enhancing customer satisfaction and operational efficiency at Sukmajaya Laundry.